The complex interplay between diabetes mellitus and atrial fibrillation. (2nd September 2022) - Yildiz, Mehmet; Lavie, Carl J.; Morin, Daniel P.; Oktay, Ahmet Afsin
ABSTRACT: Introduction: A growing body of evidence suggests that diabetes mellitus (DM) is associated with an increased risk of new-onset atrial fibrillation (AF) and contributes to suboptimal arrhythmia control and poor prognosis in patients with AF. The high prevalence of AF among patients with DM is primarily attributed to common risk factors, shared pathophysiological mechanisms, and associated atrial remodeling and autonomic dysfunction. Areas covered: This comprehensive review covers the current data on the role of DM in the development and prognosis of AF. In addition, we review the impact of anti-DM medications on AF prevention and the role of anticoagulation in patients with coexisting DM and AF. Expert opinion: DM is independently associated with new-onset AF, and the coexistence of these two conditions contributes to poor outcomes, from reduced quality of life to increased risks of thromboembolic events, heart failure, and mortality. Despite this strong link, the current evidence is insufficient to recommend routine screening for AF in patients with DM. Although some observations exist on preventing AF with anti-DM medications, randomized controlled trials are warranted to explore the proposed benefits of novel anti-DM medicines in reducing the risk of incident AF.